2018
DOI: 10.5194/bg-15-2033-2018
|View full text |Cite
|
Sign up to set email alerts
|

Shrub type dominates the vertical distribution of leaf C : N : P stoichiometry across an extensive altitudinal gradient

Abstract: Abstract. Understanding leaf stoichiometric patterns is crucial for improving predictions of plant responses to environmental changes. Leaf stoichiometry of terrestrial ecosystems has been widely investigated along latitudinal and longitudinal gradients. However, very little is known about the vertical distribution of leaf C : N : P and the relative effects of environmental parameters, especially for shrubs. Here, we analyzed the shrub leaf C, N and P patterns in 125 mountainous sites over an extensive altitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…Shrubs are defined as medium-sized woody or small plants and are distinguished from trees by their short height (below 5 m) and multiple stems [ 37 ]. The patchy distribution and large differences in shrub size lead to large within-stand variations in biomass.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrubs are defined as medium-sized woody or small plants and are distinguished from trees by their short height (below 5 m) and multiple stems [ 37 ]. The patchy distribution and large differences in shrub size lead to large within-stand variations in biomass.…”
Section: Methodsmentioning
confidence: 99%
“…The geographic information (longitude, latitude, and altitude) of the sample sites was recorded using a global positioning system (GPS). MAP and MAT were obtained for each site from the China Meteorological Forcing Dataset with a spatial resolution of 0.1° × 0.1° in latitude and longitude and every 3 h from 1981 to 2008 [ 37 , 39 , 40 ]. Considering the varied and complicated topography and different drought conditions in Southwest China, we also analysed how the biomass changed with the drought index (reconnaissance drought index, RDI).…”
Section: Methodsmentioning
confidence: 99%
“…the C:N:P ratio) has been widely used to infer nutrient limitation, biogeochemical cycle, and responses to environmental change (Elser, Fagan, Kerkhoff, Swenson, & Enquist, ; Sardans, Rivas‐Ubach, & Peñuelas, ). Previous studies have largely investigated C:N:P stoichiometry in leaves (Elser et al, ; Han, Fang, Reich, Ian Woodward, & Wang, ; Reich & Oleksyn, ; Sardans et al, ; Townsend, Cleveland, Asner, & Bustamante, ; Zhao, Reich et al, ). In contrast, much less is known about the C:N:P stoichiometry of roots, especially for fine roots (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Chave et al [60] found that annual rainfall did not explain any variation in annual litterfall from a meta-analysis of 81 South American tropical forest sites. Therefore, there were no precipitation or lagged precipitation effects on litterfall production in the stands without a seasonal shortage of water supply [17,61].…”
Section: Litterfall Production and Climatic Variablesmentioning
confidence: 96%
“…Other climatic factors, such as temperature, appear to be a partial driver of variations in senesced-leaf N and P [15], and thermal environment can also influence geographic patterns in leaf N and P [16]. In contrast, drought severity was also a key climatic factor correlated with leaf N and P, which was more appropriate for evaluating the impact of water status than precipitation [17].…”
Section: Introductionmentioning
confidence: 97%